Training for ethical linguistics: a model for building “responsible conduct of research” into department culture - Dobrin Lise M. (Linguistics)
What aspects of a linguist’s work should be covered in training for ethical linguistics? Are they specific to the study of language? Specific to the treatment of research subjects? Specific to the practice of research? Having a clear answer is a necessary first step in planning an effective ethics education program. Related questions are which institution(s) should take responsibility for it and what settings will be most conducive to ethical learning. Should training take place in the classroom, the research lab, the department, professional society meetings? Inspired by the “Responsible Conduct of Research” U.S. regulatory framework, this article presents an approach to department-level ethics education that moves beyond individual compliance and instead has as its goal the cultivation of a next generation of linguists who are able to identify and respond to the ethical issues that arise in all aspects of the work that they do.